Uso do geoprocessamento no estudo da produção agropecuária da microrregião geográfica de Carazinho RS (2002) - Castanho, Roberto Barboza (2006)
The objective of this work was know the agricultural space of the municipal districts of the Microrregião Geográfica (MRG) of Carazinho, Southern Brazil, northwest of Rio Grande do Sul State, using geoprocessing techniques. This region is important area agricultural. For the elaboration of the maps was used base agricultural data of the IBGE, year 2002, digital cartographic base, year 2000, referring data to the landed structure of INCRA, year 1998, of 18 municipal districts of the MRG and software Arcview 3.2a. The thematic maps and graphic representation of sections, bars, points and colors of geographical space show the agricultural production, with of soy, corn, wheat, etc., and quantity of animals. One map was generated to represent the land use of the MRG. Considered satisfactory obtained results, because this region have a diversity of data and was possible to represent with the selected software, representing well the reality geographical space analyzed.